A brain within the heart: A review on the intracardiac nervous system. (June 2018) - Durães Campos, Isabel; Pinto, Vitor; Sousa, Nuno; Pereira, Vitor H.
Abstract: Cardiac function is under the control of the autonomic nervous system, composed by the parasympathetic and sympathetic divisions, which are finely tuned at different hierarchical levels. While a complex regulation occurs in the central nervous system involving the insular cortex, the amygdala and the hypothalamus, a local cardiac regulation also takes place within the heart, driven by an intracardiac nervous system. This complex system consists of a network of ganglionic plexuses and interconnecting ganglions and axons. Each ganglionic plexus contains numerous intracardiac ganglia that operate as local integration centres, modulating the intricate autonomic interactions between the extrinsic and intracardiac nervous systems. Herein, we summarize the current understanding on the intracardiac nervous system, and acknowledge its role in the pathophysiology of cardiovascular diseases. Highlights: The intracardiac nervous system (ICNS) plays a crucial role in cardiac physiology. Cardiovascular diseases (CVD) cause pathological changes in intracardiac neurons. More studies are needed in this area in order to know how ICNS can underpin CVD. A better understanding of the ICNS may help to develop new treatments for CVD. This paper reviews the role and current knowledge of ICNS in CVD.